Environmental provisions in trade agreements: promises at the trade and environment interface - Axel Berger; Clara Brandi; Dominique Bruhn (Deutsches Institut für Entwicklungspolitik (DIE), 2017)
Until recently, environmental concerns have played only a marginal role in trade policy. The rulebook of the World Trade Organization (WTO) rarely touches upon environmental concerns and mainly features an exception clause for the protection of the environment (GATT, Art. XX). However, the rising number of modern preferential trade agreements (PTAs) covers an ever-broader array of policy areas, going far beyond the traditional reduction of tariffs by also including environmental provisions. Numerous PTAs negotiated on a bilateral and regional basis have comprehensive “green” components. For example, many PTAs include obligations not to lower environmental standards, the right to regulate for the benefit of the environment, and the commitment to implement multilateral environmental agreements. The inclusion of environmental provisions can spark controversies. For some, the inclusion of environmental provisions offers untapped potential for actual environmental protection, making these agreements more compatible with environment and climate policies. However, trade critics often see these provisions as mere “fig leafs” that are included in modern PTAs in order to make them less controversial in the eyes of the public and legislators. For other critics, they represent an instrument of “green protectionism” in order to keep cheaper products from developing countries out of the market. Given the newness of the widespread inclusion of environmental provisions in PTAs and the heated debate that is raging about the nature and effects of trade policies, better data and research is needed to understand and analyse this development. Firstly, we need to improve our understanding of the specific design of these new rules and the related policy initiatives of PTA signatories. What drives the inclusion of environmental provisions in trade agreements? Which are the most innovative agreements and which the most innovative countries in terms of including environmental provisions in PTAs? Which environmental provisions are diffused more often than others into subsequent PTAs? Secondly, there is a need to understand the interplay between PTAs and other environmental or climate agreements. To what extent do PTAs with environmental provisions serve the purpose of multilateral environmental agreements (MEAs) or the Paris Agreement on climate change? Last but not the least: What are the implications of environmental provisions? Does the inclusion of these provisions in PTAs help the contracting parties to implement domestic environmental laws? The innovative and interactive online tool TREND analytics based on the Trade & Environment Database (TREND), which tracks almost 300 different environmental provisions in the texts of about 630 PTAs, offers new ways of going further and of undertaking research to generate fine-grained information on the interplay between trade and the environment, providing fresh insights into a number of relevant policy discussions. This Briefing Paper summarises recent research results based on TREND, along with providing new insights into these questions and policy discussions at the interface of international trade and the environment.
Keywords: 330; Handel und Investitionen; Klimawandel